The effect of temperature on somatic and gonadal development of the sea urchin Paracentrotus lividus (Lamarck, 1816) - Santos, Pedro M. (2020)
The common sea urchin Paracentrotus lividus (Lamarck, 1816) is the most consumed echinoid in Europe. It is considered a seafood delicacy, given its high-valued gonads. In sea urchins, temperature probably represents the most important abiotic factor affecting several physiological processes and it is essential to better establish optimal reference conditions for aquaculture. In this study, four rearing temperatures (18 °C, 20 °C, 22 °C and 24 °C) were tested in wild-caught adult P. lividus, from the west coast of Portugal. The animals were fed an agarbased artificial diet, over a period of 90 days. The effect of temperature was tested in terms of test diameter and total wet weight, feed intake, gonadosomatic index (GI) and reproductive development. Thus, linear growth rate (mm month−1), daily growth rate (% day−1), total wet weight gain (mg ind.−1 day−1) and total feed intake (g day−1 ind.−1) of sea urchins were calculated at the end of the trial. Although feed intake was relatively similar between groups, the results showed a consistent response for biometric parameters regarding the different temperatures regimes. The rearing temperature of 22 °C promoted the highest test diameter (.53 mm month−1) and total wet weight (47 mg ind.−1 day−1) growth. Sea urchins from the same group (22 °C) presented the highest final GI of 9.3%, a 163.5% increase in comparison to the initial value, after the fasting period (3.5%). This temperature also promoted the highest gonad maturation levels, both in males and females. Although increasing temperatures (until 22 °C) generally produced favourable rearing results, the 24 °C regime led to lower somatic and gonadal growth, plus slower gonad maturation results. Overall, P. lividus fed with a formulated diet and reared at 20–22 °C, showed considerable somatic and gonadal growth, as well as a significant sexual maturation, which will allow to obtain developed gonads and gametes all year round. On the other hand, 18 °C promoted a slower progression in the gametogenic cycle, which may contribute to produce gonads with better organoleptic properties for human consumption.